2002
DOI: 10.1080/0028825x.2002.9512771
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plant light environment on mycorrhizal colonisation in field‐grown seedlings of podocarp‐angiosperm forest tree species

Abstract: To test the possibility that the development of mycorrhizas in seedlings may be limited under shaded conditions, arbuscular mycorrhizal colonisation was measured in gap and understorey seedlings from mixed podocarp/angiosperm forests in North Okarito, south Westland, and Blue Duck Scientific Reserve, Marlborough, New Zealand. Mean percentage colonisation of seedlings of podocarp and angiosperm tree species ranged from 66 to 97% of root length, and no seedlings were nonmycorrhizal. Plant light environment had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
(35 reference statements)
1
16
1
1
Order By: Relevance
“…Indeed, as shown in previous studies (Hurst et al. , Dickie and Holdaway ), AMF infection of conifer (podocarp) roots is generally extremely dense. For example, Hurst et al.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Indeed, as shown in previous studies (Hurst et al. , Dickie and Holdaway ), AMF infection of conifer (podocarp) roots is generally extremely dense. For example, Hurst et al.…”
Section: Discussionsupporting
confidence: 62%
“…Indeed, as shown in previous studies (Hurst et al 2002, Dickie andHoldaway 2011), AMF infection of conifer (podocarp) roots is generally extremely dense. For example, Hurst et al (2002) reported infection levels of 88-96% of root length of New Zealand temperate podocarps. This type of root structure specific to podocarps (or Araucariaceae), dense AMF infections and the compositions of the mycorrhizal fungal community specific to podocarps (or Araucariaceae) might explain the finding that AMassociated conifers are more efficient in N uptake than EM-associated trees in our study.…”
Section: Conifer Abundancementioning
confidence: 99%
“…1963; Russell et al . 2002), which efficiently take up phosphate, the majority of angiosperm species in mixed lowland rain forests are also heavily infected (Hurst et al . 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Enright & Ogden 1995). However, although podocarps are heavily infected with endomycorrhizal associates (Baylis et al 1963;Russell et al 2002), which efficiently take up phosphate, the majority of angiosperm species in mixed lowland rain forests are also heavily infected (Hurst et al 2002).…”
Section:      mentioning
confidence: 99%
“…Nesses ambientes, disponibilidade de luz, de água e de nutrientes varia no tempo e espaço e é considerado o fator abiótico que mais afeta o estabelecimento das plântulas (EVANS e EDWARDS, 2001). A capacidade da espécie em adequarse morfológica e fisiologicamente às variações na disponibilidade de recursos e em associar-se com fungos micorrízicos arbusculares (FMA) favorece o estabelecimento de plantas em ambientes limitantes em água e luz (EVANS e EDWARDS, 2001;HURST et al, 2002). No entanto, também a associação micorrízica entre raízes e FMA é influenciada, entre outros fatores, pela intensidade de luz (GEHRING, 2003) e pela disponibilidade de água (ENTRY et al, 2002).…”
Section: Introductionunclassified